Auditory Neuropathy: Clinical Evaluation and Diagnostic Approach - Carvalho, Guilherme Machado; Leão, Beatriz Prista; Ramos, Priscila Zonzini; Guimarães, Alexandre Caixeta; Castilho, Arthur Menino; Sartorato, Edi Lúcia (Acta Médica Portuguesa, 2016)
Introduction: Auditory neuropathy is a condition in which there is a change in the neuronal transmission of the auditory stimuli. Our objective was to describe the patients’ series within the clinical spectrum of auditory neuropathy. Material and Methods: We designed a transversal, retrospective study, with a description of a consecutive case series. Auditory neuropathy was defined by the presence of acoustic otoemissions plus absent/abnormal auditory brainstem responses with cochlear microphonism. Results: 34 patients with bilateral hearing loss, 23 males and 11 females, were included in the study. Eighty percent of the cases had congenital onset of hearing loss. Acoustic otoemissions were absent in 67% of them. Cochlear microfonism was present in 79% of all cases. Prenatal, perinatal or ambiental factors were present in 35.2% of the cases. Discussion: Medical literature shows great variability in findings related to auditory neuropathy, both in its etiology and epidemiological data. Conclusion: Auditory neuropathy presents a broad spectrum of changes that may result from mild to severe changes in the functioning of the auditory pathway, and in our sample we observed that 80% of Auditory neuropathy have congenital onset of hearing loss and/or with cochlear microphonism identified. 91% of patients experience significant hearing impairment and 53% suffer from severe or profound deafness.